Análise da densidade mineral óssea de idosas praticantes de hidroginástica e não praticantes de exercício físico : um estudo transversal - Carvalho, Marcus Vinicius Marinho de (2015)
Aging is associated with multiple anatomical and physiological changes that can lead to disability, bone fragility and osteoporosis. It is known that exercise can help improve bone mineral density (BMD). The objective of this study was to compare the BMD of elders that practices aquatic exercise, for at least three years, with elders not practitioners of physical exercise. The sample was 67, allocated in two groups: Practitioner Aquatic Exercise (PH, n = 30) and Non-Practitioner Physical Activity (NP, n = 37). Data collection was conducted in May 2014 at the Clinic CEMISE in Aracaju. The assessment instruments were: SF-36, IPAQ, Functional Independence Measure (FIM) and DEXA. For statistical analysis, the Shapiro-Wilk test was used, chi-square,tthe Student, Mann-Whitney and Anova two way test (p < 0.05). When comparing 2011 and 2014, it was found that the PH group showed a significant increase in BMD in the total femur (p < 0.001); while the NP, a decrease (p < 0.001); PH group had, in 2014, BMD higher in total femur (p < 0.001) than the NP. There was no significant difference between groups in the eight domains of SF-36 as well as in MIF (p = 0.590). IPAQ´ value in PH was significantly higher than in NP group (p < 0.001). It is concluded that older practitioners of aquatics exercises had higher BMD only in total femur segment, as well as level of physical exercise. However the quality of life and functional independence of both groups were similar.